Polymeric-Micelle-Based Delivery Systems for Nucleic Acids - Genada Sinani; Meltem Ezgi Durgun; Erdal Cevher; Yıldız Özsoy (MDPI AG, 2023)
Nucleic acids can modulate gene expression specifically. They are increasingly being utilized and show huge potential for the prevention or treatment of various diseases. However, the clinical translation of nucleic acids faces many challenges due to their rapid clearance after administration, low stability in physiological fluids and limited cellular uptake, which is associated with an inability to reach the intracellular target site and poor efficacy. For many years, tremendous efforts have been made to design appropriate delivery systems that enable the safe and effective delivery of nucleic acids at the target site to achieve high therapeutic outcomes. Among the different delivery platforms investigated, polymeric micelles have emerged as suitable delivery vehicles due to the versatility of their structures and the possibility to tailor their composition for overcoming extracellular and intracellular barriers, thus enhancing therapeutic efficacy. Many strategies, such as the addition of stimuli-sensitive groups or specific ligands, can be used to facilitate the delivery of various nucleic acids and improve targeting and accumulation at the site of action while protecting nucleic acids from degradation and promoting their cellular uptake. Furthermore, polymeric micelles can be used to deliver both chemotherapeutic drugs and nucleic acid therapeutics simultaneously to achieve synergistic combination treatment. This review focuses on the design approaches and current developments in polymeric micelles for the delivery of nucleic acids. The different preparation methods and characteristic features of polymeric micelles are covered. The current state of the art of polymeric micelles as carriers for nucleic acids is discussed while highlighting the delivery challenges of nucleic acids and how to overcome them and how to improve the safety and efficacy of nucleic acids after local or systemic administration.